Kontribusi Zakat Terhadap Mobilitas Sosial Ekonomi pada Masa Kepemimpinan Rasulullah SAW di Madinah - Zahira, Nazhan; Binti Ahmad, Putri Afiqah; Febrina, Dwi; Dinata, Agfahmi; Hayati, Fitri (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to examine the contribution of zakat to socio-economic mobility during the leadership of the Prophet Muhammad SAW in Madinah, emphasizing its role not merely as a religious obligation but also as a strategic instrument for social transformation. Employing a qualitative method through literature review, this research explores historical accounts, Islamic economic literature, and academic sources related to zakat management. The findings reveal that zakat, when administered systematically and empowerment-oriented, effectively reduced social inequality, improved the living standards of marginalized communities, and promoted sustainable social mobility. The productive zakat model introduced by the Prophet SAW not only succeeded in establishing social justice in Madinan society but also laid the foundation for an economy based on communal solidarity. These results highlight the relevance of the Prophetic zakat model as an alternative solution for addressing contemporary socio-economic challenges, particularly in promoting equitable and sustainable development.